Structural and functional characterisation of compositionally optimised rice bran and lingonberry dietary fibre‐based gel‐type product enriched with phytochemicals. (29th June 2020) - Zadeike, Daiva; Vaitkeviciene, Ruta; Marksa, Mindaugas; Juodeikiene, Grazina; Bendoraitiene, Joana; Bartkiene, Elena; Lele, Vita; Viskelis, Pranas; Bernatoniene, Jurga; Jakstas, Valdas
Summary: In this study, the model gel‐type delivery system containing rice bran (RB), lingonberry ( Vaccinium vitis‐idaea L.) press cake (LPC) and thyme essential oil ( Thymus vulgaris L.), was developed and evaluated by their texture, gelation rate and antioxidant activity changes during storage and simulated gastrointestinal digestion. For the structuring of the gel‐type RB‐LPC matrix, a high‐intensity ultrasound (850 kHz; 1.3 W cm −2 ) treatment at 40 °C was applied. The release of total phenols and flavonoids was measured during digestion process by a spectrophotometric method and reversed‐phase high‐performance liquid chromatography (RP‐HPLC), respectively. The contributions of xanthan and alginate as gelling agents to improve the stability of the gel texture protecting it from fast degradation under gastrointestinal digestion enable a controlled release of antioxidants, thus improving their biodistribution. Storage temperature influenced the reduction of antioxidant activity in gels depending on stabiliser used, with the lowest values from those with alginate when stored for 28 days at 4 °C. This knowledge can be used to facilitate the selection of the most appropriate plant polysaccharide‐based delivery system for specific applications. Abstract : High‐intensity ultrasound is suitable for RB‐LPC gel structuring. The RB‐LPC network maintains a possible delivery system for phenols. Immobilised EOE preserves more stable antioxidant activity in RB‐LPC gels. Alginate ensures the controlled release of flavonoids.